Fungal volatiles: an environmentally friendly tool to control pathogenic microorganisms in plants. (2nd January 2016) - Schalchli, H.; Tortella, G. R.; Rubilar, O.; Parra, L.; Hormazabal, E.; Quiroz, A.
Abstract: Fungi are an extraordinary and immensely diverse group of microorganisms that colonize many habitats even competing with other microorganisms. Fungi have received recognition for interesting metabolic activities that have an enormous variety of biotechnological applications. Previously, volatile organic compounds produced by fungi (FVOCs) have been demonstrated to have a great capacity for use as antagonist products against plant pathogens. However, in recent years, FVOCs have been received attention as potential alternatives to the use of traditional pesticides and, therefore, as important eco-friendly biotechnological tools to control plant pathogens. Therefore, highlighting the current state of knowledge of these fascinating FVOCs, the actual detection techniques and the bioactivity against plant pathogens is essential to the discovery of new products that can be used as biopesticides.